SURVEY OF DISTRICT LIBRARIES IN LOWER ASSAM - Kankana Chakraborty (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The main purpose of this paper is to give an overview of the public library system in Assam. The present scenario of the district libraries of Assam also included in this paper. For the survey, there are total three districts are selected from lower Assam. And the interview method is used to collect relevant data from the library professionals. Various primary and secondary literatures are also studied to gain the knowledge about public library system in Assam. The finding of the study reveals that the condition of the district libraries of Assam is not very impressive. Though these three public libraries are rich in regard to their collection and staff, but the number of daily users of the district libraries is not as par the expectation. And most of users visit the library for reading newspapers. The finding also shows that due to the lack of the funds as well as government initiative the libraries are not fulfill the requirements of the users of the libraries. One more important finding is that the libraries are lacking behind in terms of using modern technologies like computer and internet etc. which becomes a basic need of today’s generation.